The Sixth Day - Coulter, Catherine (New York : Gallery Books, 2018)
"Special agents Nicholas Drummond and Michaela Caine take on a ruthless mastermind in the fifth highly anticipated thriller in the New York Times bestselling A Brit in the FBI series. When several major political figures die mysteriously, officials declare the deaths are from natural causes. Then the German Vice-Chancellor dies on the steps of 10 Downing Street, and a drone is spotted hovering over the scene. The truth becomes clear--these high-profile deaths are well-constructed assassinations, and the Covert Eyes team is tasked to investigate. With the help of Dr. Isabella Marin, a young expert in the enigmatic Voynich Manuscript and cryptophasia (twin language), Nicholas and Michaela home in on Roman Ardelean, a wealthy cybersecurity genius and a descendant of fifteenth century Romanian Vlad the Impaler--often romanticized as Dracula. Ardelean believes the Voynich Manuscript will unlock the secret to curing his severely ill twin brother's blood disorder and is willing to murder anyone who gets in his way, including Nicholas and Michaela. Along with MI5, the Covert Eyes team must race against the clock to find Ardelean before he unleashes a devastating attack on London intended to destroy those he believes betrayed him. With heart-pounding tension and gripping suspense, New York Times bestselling authors Catherine Coulter and J.T. Ellison "are really on an amazing roll with their outstanding A Brit in the FBI series" (RT Book Reviews)"--
"Special agents Nicholas Drummond and Michaela Caine take on a ruthless mastermind in the fifth highly anticipated thriller in the New York Times bestselling A Brit in the FBI series"--
Adult
Keywords: United States -- Federal Bureau of Investigation -- Fiction; Intelligence officers -- Fiction; Spy stories; Mystery fiction; Suspense fiction; Mystery fiction